The effects of perceived decision-making styles on evaluations of openness and competence that elicit collaboration - TSAI, Ming-Hong (Institutional Knowledge at Singapore Management University, 2019)
When interacting with a task partner, individuals often rely upon characteristics they infer about their partner to determine their level of collaboration with the partner. To explore social perception processes related to collaboration, we examined perceptions of an actor’s decision-making style as predictors. Using different methods in various research settings, we found that compared with perceptions of an actor’s intuitive decision-making style or of a nonspecific decision-making style, perceptions of an actor’s rational decision-making style were more positively associated with inferences of the actor’s openness and competence, both of which were in turn associated with the perceiver’s collaborative intention with the actor. Intentions to engage in mutual collaboration were also positively associated with performance in an idea generation task. Therefore, our research offers a novel illustration of how to enhance collaboration based on perceptions of openness and competence inferred from others’ rational rather than intuitive decision-making style.